STRATEGIES TO IMPROVE THE QUALITY OF CARDIOPULMONARY RESUSCITATION (CPR): A LITERATURE REVIEW - Widya Addiarto; Rizka Yunita (NHM PRESS, 2023)
Background: Nowadays, the incidence of cardiac arrest affects about 135 million people with the survival rate ranges from 2% to 11%. Seeing the trend of the incidence of cardiac arrest that occurred at this time, the necessary steps for appropriate treatment increased the survival rate of cardiac arrest patients performing well in CPR. Increasing the high quality of CPR gives a great impact on patient safety in both cardiac arrest outside and inside the hospital. The aim of this study was to identify the strategies to improve high quality of CPR. Methods: This literature review was done by collecting and analyzing articles concerned on high quality CPR. Articles were collected through electronic databases: EBSCOhost, ProQuest and Science Direct used keywords about CPR, high quality CPR, and cardiac arrest. A number of research articles were reviewed and the criteria of articles was full text and published between 2009 until 2021. Results: The important strategies in achieving indicators of high quality CPR are: correct patient position, using hand dominant position, turn over the rescuer position, body mass index and body posture, using video simulation, and using music to maintain the correct rhythm during CPR. Conclusion: High quality CPR is essential to apply both intra or out of hospital to maintain the survival rate of cardiac arrest patients. Therefore, using a strategy is expected to improve skill and outcome of high quality CPR.